2005
DOI: 10.1007/s00775-005-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on imidazole heme conformations

Abstract: Density functional theory computations of heme with ionized propionic acid groups, axially coordinated with two imidazoles, were performed for different mutual orientations of the imidazole planes. Environmental influences from water or protein were considered with a continuum dielectric medium by solving the Poisson equation. In vacuum, optimized geometries yielded imidazole-heme conformations where the NH groups of imidazoles are oriented toward the heme propionic groups in agreement with data from crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 68 publications
1
37
0
Order By: Relevance
“…The standard free energy of reduction can be calculated routinely using the thermodynamic cycle 34,35 describing the relation between the electron attachment process in vacuum [gas phase, (g)] and the corresponding reduction in solution (see Fig. 1).…”
Section: Computation Of Redox Potentialsmentioning
confidence: 99%
“…The standard free energy of reduction can be calculated routinely using the thermodynamic cycle 34,35 describing the relation between the electron attachment process in vacuum [gas phase, (g)] and the corresponding reduction in solution (see Fig. 1).…”
Section: Computation Of Redox Potentialsmentioning
confidence: 99%
“…In our previous work we studied orientations of imidazoles axially *Address correspondence to this author at the Department of Chemistry, University of Belgrade, Belgrade, Serbia; Tel: +381113336605; E-mail: szaric@chem.bg.ac.rs coordinated to iron-porphyrin [15][16][17][18]. It was shown that the noncovalent interactions with the propionic groups are very important for the orientations of the imidazoles and that the conformations of the propionic groups have strong influence on these interactions [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Negatively charged propionic groups of heme porphyrin can make strong hydrogen bonds and these bonds can determine conformations of the groups. As it was mentioned above, the conformations of the propionic groups greatly influence the orientation of axially coordinated imidazoles [15,17]. We used a nonredundant database of the Protein Data Bank (PDB), with 3,398 protein chains to examine systematically the occurrence and the role of hydrogen bonds and hydrophobic interactions of porphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…Among other factors, noncovalent interactions can also influence the properties of metalloporphyrins [5,[9][10][11]. Metalloporphyrins can form several types of noncovalent interactions, some of them involving extended π-system of a porphyrin.…”
Section: Introductionmentioning
confidence: 99%